Real-Life Active Surveillance of a Naphazoline/ Hypromellose Fixed Combination’s Safety Profile in Peruvian Population - Contreras-Salinas H; Barajas-Hernández M; Baiza-Durán LM; Orozco-Ceja V; Rodríguez-Herrera LY (Dove Medical Press, 2021)
Homero Contreras-Salinas, Mariana Barajas-Hernández, Leopoldo Martín Baiza-Durán, Vanessa Orozco-Ceja, Lourdes Yolotzin Rodríguez-Herrera Pharmacovigilance Department, Laboratorios Sophia S.A. de C.V., Zapopan, Jalisco, MéxicoCorrespondence: Lourdes Yolotzin Rodríguez-Herrera Tel +52 3001 4200 ext 1188Email lourdes.rodriguez@sophia.com.mxObjective: Identifying the adverse reactions and the possible risks associated with the use of naphazoline 0.1% + hypromellose 0.5% (NAPH), thereby evaluating its tolerability and safety profile.Methods: A total of 236 Peruvian patients were included in an active pharmacovigilance study drug event monitoring consisting in 2 phone calls conducted in order to register adverse drug reactions (ADRs), the product's tolerability and to assess the risk concerning specific clinical and demographic characteristics using a binary logistic regression model.Results: A total of 54 ADRs (one per patient) were reported after the use of NAPH; classified (according to the Medical Dictionary for Regulatory Activities) into two groups of System Organ Class (SOC): eye disorders and nervous system disorders; and four groups of preferred term (PT): eye irritation, vision blurred, eye pruritus and headache. All ADRs were expected, mild and not serious. No risk factors related to the clinical and demographic characteristics of the patients were identified.Conclusion: The low incidence of ADRs, their short recovery time, and their categorization as "mild" and "not serious" demonstrates the high tolerability in the studied population; therefore, according to the study, the safety profile for NAPH seems to be adequate, with a suitable tolerability.Keywords: pharmacovigilance, naphazoline, hypromellose, adverse drug reaction, drug event monitoring